Impedance audiometric results for the different probe tones. - K, Sridharan (Journal of All India Institute of Speech and Hearing)
Impedance Audiometry yields information quickly and it does not require judgements by the patient. Low frequency probe tones are insensititive to identify. and differentially diagnose few pathological conditions. High-frequency probe-tones provide additional information and help us to identify those pathological conditions which do not always yield pathognomonic patterns with conventional tympanometry (which use low-frequency probe-tones). Hence diagnostic findings for the different probe-tones need to be compared. Present study is carried out to compare the results obtained using the high frequency probe tones and low frequency probe-tones.